2000
DOI: 10.1007/bf03024863
|View full text |Cite
|
Sign up to set email alerts
|

Cumulation characteristics of cisatracurium and rocuronium during continuous infusion

Abstract: Purpose: The dissimilar pharmacokinetic properties of cisatracurium (CIS) and rocuronium (ROC) predict different potential for drug cumulation when these drugs are administered by continuous infusion. A study was therefore undertaken to compare cumulation potential of CIS and ROC during surgical procedures of relatively long duration (2-4 hr). Methods: Sufentanil/propofol-N 2 O anesthesia was administered to 40 ASA I and II adults. In a double-blind protocol, patients were randomly allocated to receive a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The same phenomenon has been reported in other infusion studies with mivacurium, 11,15 cisatracurium, 16 rocuronium, 16 atracurium 17 and vecuronium. 17 Infusion rates are relatively high when the patient recovers from a bolus dose, as occurred in all the above studies, because enough drug had to be provided not only to maintain blockade, but also to prevent recovery from the bolus dose.…”
Section: Méthode : Chez 48 Patients Consentants Classifiés Asa I Ou supporting
confidence: 86%
“…The same phenomenon has been reported in other infusion studies with mivacurium, 11,15 cisatracurium, 16 rocuronium, 16 atracurium 17 and vecuronium. 17 Infusion rates are relatively high when the patient recovers from a bolus dose, as occurred in all the above studies, because enough drug had to be provided not only to maintain blockade, but also to prevent recovery from the bolus dose.…”
Section: Méthode : Chez 48 Patients Consentants Classifiés Asa I Ou supporting
confidence: 86%
“…The suitability of rocuronium for continuous infusion is well known, but the optimal rate of administration of a continuous infusion of rocuronium has not yet been clearly defined. Several studies have reported that the dose of rocuronium required to induce muscle relaxation does not decrease over time [2,4,5]. The differences among individuals in terms of their sensitivity to neuromuscular blocking agents in general and rocuronium in particular may be affected by several factors.…”
Section: Introductionmentioning
confidence: 97%
“…However, the continuous administration of drugs provides a more stable blood concentration and is more useful in maintaining patient stability under conditions with varying requirements, such as during surgery. Continuous infusions of rocuronium within a short period do not result in accumulation of the drug [2], and its administration for longer durations in intensive care patients results in only a moderately prolonged recovery time [3].…”
Section: Introductionmentioning
confidence: 99%
“…Rocuronium is suitable for continuous infusions as there are no active metabolites produced. Short duration infusions have been shown not to accumulate in humans following continuous infusion (Miller et al. 2000) and longer durations (greater than 5 hours) resulted in only a moderately prolonged recovery time (Sparr et al.…”
Section: Introductionmentioning
confidence: 99%